2004
DOI: 10.2320/matertrans.45.2403
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Detection of Cold Flakes in Aluminum Alloy Die-Cast Plate with Ultrasonic Measurement

Abstract: Aluminum alloy die-cast plates (ADC 12) were subjected to ultrasonic measurement to obtain a relation between the intensity distribution of the ultrasonic wave and positions of cold flakes appearing in the plate for developing a nondestructive method to detect cold flakes in the diecasts. Die-cast plates of 170 mm in length, 50 mm in width and 6.8 mm in thickness were produced with wider gates to introduce larger cold flakes in the plate. Then the ultrasonic measurement was carried out with the immersion metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Typically, there are two types of noncontact ultrasonic techniques: water immersion ultrasonic [ 11 , 12 , 13 , 14 , 15 , 16 ] and noncontact laser ultrasonic. The water immersion ultrasonic technique is mostly performed on small objects with uneven surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, there are two types of noncontact ultrasonic techniques: water immersion ultrasonic [ 11 , 12 , 13 , 14 , 15 , 16 ] and noncontact laser ultrasonic. The water immersion ultrasonic technique is mostly performed on small objects with uneven surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors [4,5] carried out the ultrasonic measurement and the acoustic microscopy of aluminum alloy die-cast (ADC12) plates containing cold flakes, to show that the oxide layer and the body of the cold flakes can be detected as bright or dark regions in the acoustic image, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…27) Although many efforts have been done to eliminate cold flakes, no success has been attained to eliminate them completely from die-cast products. 28) Recently, the authors 29,30) carried out the ultrasonic measurement and the acoustic microscopy of aluminum alloy die-cast plate (ADC12) containing cold flakes, and it was found that the oxide layer and the body of the cold flake were observed as bright and dark regions in the acoustic image, respectively. The authors 30) also carried out the bending test, and showed that a crack propagated through the coarse cold flake directing transversely to the bending stress.…”
Section: Introductionmentioning
confidence: 99%